Internship at Public Institution Marceliano Polo (2020)
This report details an internship executed at public institution Marceliano Polo in Cereté-Córdoba. In this report I share how was my personal experience as a novice teacher and the things I had to deal with during all this process, I also mentioned my experience with the implementation of virtual classes, The current situation led us to take different measures to carry out our work as teachers. In addition, this internship aimed to implement lessons that focus on CLT to improve students’ oral skills. CLT lessons have proved to be an effective alternative to develop more dynamic and fluent lessons. This approach has been used for the development of communicative skills. Hence, the purpose of this internship was to identify the possible improvements in students’ oral skills after the implementation of CLT lessons.